(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Shaktism in which the highest place was accorded to the female principle was the faith of a large number of people all over the continent. The goddess of Shakti was worshipped with different names: most popular was the mother goddess. The origin of Shaktism evolved out of the pre-historic mother goddess cult symbolizing the facts of primitive life.